PENGARUH KREATIVITAS DAN PROFESIONALISME TERHADAP KEGIATANPEMBELAJARAN GURU IPS SEJARAH SMP DI KAB SUKOHARJO - Hariyani, Sri; Waluyo, Herman J.; Agung S., Leo (HISTORIKA, 2016)
The quality of education has been only in the spotlight in the eyes of our society. Professionalism and creativity of teachers considered to be a variable that has a relationship with the quality of education. The purpose of this study to analyze the level of professionalism and creativity of teachers in learning activitiesIn this study, experiments were conducted on a social studies teacher at the junior high school history Sukoharjo in the year 2011/2012. The samples in this study is done by using the all populations. The data analysis technique used is a two way analysis of variance.Results: In this study indicate that: 1) there was no significant effect on the level of creativity of learning activities on social studies teacher of History in Sukoharjo; 2) there is a significant effect on the activity level of professionalism of teachers teaching in social studies teachers in the history of Sukoharjo year 2011/2012; 3) there was no significant effect of the interaction level of creativity and professionalism of teachers on learning activities History Social Studies teacher in Sukoharjo 2011 / 2012.Implikasi this study by its level of creativity and professionalism can improve the learning activities in a social studies teacher of History. Thus the learning achievement History IPS can be improved through enhanced learning activities organized by the teacher.